The Drosophila MLR COMPASS complex is essential for programming cis-regulatory information and maintaining epigenetic memory during development. Issue 7 (13th February 2020) - Zraly, Claudia B; Zakkar, Abdul; Perez, John Hertenstein; Ng, Jeffrey; White, Kevin P; Slattery, Matthew; Dingwall, Andrew K
Abstract: The MLR COMPASS complex monomethylates H3K4 that serves to epigenetically mark transcriptional enhancers to drive proper gene expression during animal development. Chromatin enrichment analyses of the Drosophila MLR complex reveals dynamic association with promoters and enhancers in embryos with late stage enrichments biased toward both active and poised enhancers. RNAi depletion of the Cmi (also known as Lpt) subunit that contains the chromatin binding PHD finger domains attenuates enhancer functions, but unexpectedly results in inappropriate enhancer activation during stages when hormone responsive enhancers are poised, revealing critical epigenetic roles involved in both the activation and repression of enhancers depending on developmental context. Cmi is necessary for robust H3K4 monomethylation and H3K27 acetylation that mark active enhancers, but not for the chromatin binding of Trr, the MLR methyltransferase. Our data reveal two likely major regulatory modes of MLR function, contributions to enhancer commissioning in early embryogenesis and bookmarking enhancers to enable rapid transcriptional re-activation at subsequent developmental stages.